Neuronal Organization of Deep Brain Opsin Photoreceptors in Adult Teleosts - Hang, Chong Yee; Kitahashi, Takashi; Parhar, Ishwar S. (Frontiers in Neuroanatomy, 2016)
Biological impacts of light beyond vision, i.e., non-visual functions of light, signify the need to better understand light detection (or photoreception) systems in vertebrates. Photopigments, which comprise light-absorbing chromophores bound to a variety of G-protein coupled receptor opsins, are responsible for visual and non-visual photoreception. Non-visual opsin photopigments in the retina of mammals and extra-retinal tissues of non-mammals play an important role in non-image-forming functions of light, e.g., biological rhythms and seasonal reproduction. This review highlights the role of opsin photoreceptors in the deep brain, which could involve conserved neurochemical systems that control different time- and light-dependent physiologies in in non-mammalian vertebrates including teleost fish.